Encyclopedia of RF and microwave engineering - Chang, Kai, 1948- (John Wiley, 2005)
RF and Microwave Engineering is one of the fastest growth areas of the past decade and will probably continue to be a very active area of research and application in a large variety of fields. This six volume set illustrates how this field has been the key to enabling technology responsible for the phenomenal growth of wireless communication. This set also examines how RF and microwave engineering continues to have great influence as the technology behind such important applications as radar, remote sensing, remote control, sensors, navigation, surveillance, electronic warfare, radiometers, plasma research, and imaging. --